Pengaruh Metode Ceramah terhadap Pengetahuan dan Sikap WUS dalam Pemeriksaan IVA di Puskesmas Semula Jadi Kota Tanjung Balai - Elisa Chrisnita Purba; Asriwati Asriwati (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Visual Inspection of Acetic Acid (IVA) is an early detection method for cervical cancer which is as popular as the Pap Smear. The coverage of early detection of cervical cancer in Indonesia is 136.2 per 100,000 population. The aim was to analyze the effect of the low level of the visual inspection of acetic acid on women of childbearing age at the Semulajadi Public Health Center, Tanjung Balai City. This type of research is a quasi-experimental research with the research design used is one group pre-test-post test design. The population in this study was 235 respondents with a sample size of 40 people. Data analysis used paired sample t-test. The results of this study showed that the lecture method using booklets and leaflets about IVA had an influence in increasing knowledge and attitudes with a p-value of 0.000 (0.000 <0.05). The results of the t-test group The lecture method using booklets and leaflets about IVA increased knowledge and attitudes. The Lecture method using the booklet and leaflet media is able to increase knowledge and attitudes about IVA examination by being given health promotion which can be seen from a significant value meaning that there is a significant influence that can increase knowledge and attitudes. By increasing health promotion continuously carried out by midwives, it can reduce maternal morbidity and mortality due to cervical cancer by conducting early detection, namely conducting IVA examinations